(untitled) - Rishel, James B. (New York, NY, 2006)
A reference for HVAC designers, engineers, and technicians, covering the latest methods for designing, installing, and operating both constant and variable speed pumps for HVAC systems. Contains sections on basic tools in digital electronics, computers, and systems analysis; HVAC pumps and their performance; pumps for open and closed HVAC cooling systems; pumps for hot water systems; and installation and operation. Includes glossaries of terms and equations.
Keywords: Hydronics,Pumping machinery; Equipment and supplies,Handbooks, manuals, etc; Handbooks, manuals, etc